2018
DOI: 10.1200/jco.2018.36.18_suppl.lba5009
|View full text |Cite
|
Sign up to set email alerts
|

Abi Race: A prospective, multicenter study of black (B) and white (W) patients (pts) with metastatic castrate resistant prostate cancer (mCRPC) treated with abiraterone acetate and prednisone (AAP).

Abstract: LBA5009 Background: Pivotal trials of AAP for patients with mCRPC enrolled few B pts, a population with a higher mortality from prostate cancer. Retrospective data suggests B pts may have higher PSA response rates than W pts treated with AAP for mCRPC. Therefore, we prospectively investigated AAP in B vs. W pts with mCRPC. Methods: Abi Race (NCT01940276) is a prospective, multicenter, parallel group study of AP in 100 men (50 B, 50 W) with mCRPC, self-identified by race. All pts received AA 1000 mg/D and P 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 0 publications
5
50
0
Order By: Relevance
“…Even though African American men had higher numbers of comorbidities, they still had better OS compared to white men (HR = 0.826; 95%CI [0.732-0.933]) (35). "Abi Race" (NCT01940276) is a prospective, multicenter study of African American and white patients with mCRPC treated with abiraterone acetate and prednisone, evaluating racial disparities in the outcomes (44). When George et al reported the initial results of this prospective study, they found the primary endpoint radiographic progression-free survival (rPFS) was equal among the races (16.8 months) (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though African American men had higher numbers of comorbidities, they still had better OS compared to white men (HR = 0.826; 95%CI [0.732-0.933]) (35). "Abi Race" (NCT01940276) is a prospective, multicenter study of African American and white patients with mCRPC treated with abiraterone acetate and prednisone, evaluating racial disparities in the outcomes (44). When George et al reported the initial results of this prospective study, they found the primary endpoint radiographic progression-free survival (rPFS) was equal among the races (16.8 months) (44).…”
Section: Discussionmentioning
confidence: 99%
“…“Abi Race” (NCT01940276) is a prospective, multicenter study of African American and white patients with mCRPC treated with abiraterone acetate and prednisone, evaluating racial disparities in the outcomes ( 44 ). When George et al reported the initial results of this prospective study, they found the primary endpoint radiographic progression-free survival (rPFS) was equal among the races (16.8 months) ( 44 ). Interestingly, African American men had more significant and more durable PSA progression-free survival, which was their secondary endpoint ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…3 Data from several clinical trials point in the same direction. George et al 16 reported that black men had better a progression-free survival rate compared with white men (16.6 months vs 11.5 months) when treated with abiraterone and prednisone. Moreover, a pooled analysis by Halabi et al 17 of 9 randomized clinical trials for advanced prostate cancer found that overall survival was the same for black and white men.…”
Section: Discussionmentioning
confidence: 99%
“…There was no pretreatment factor associated with the development of new unconfirmed lesions among men with mCRPC responding to enzalutamide in either setting. Although we originally hypothesized that men with more androgen-receptor-dependent prostate cancer, such as those with low Gleason scores, younger age, or African ancestry, [12][13][14] and those with fewer prior hormonal therapies would have a greater probability of pseudoprogression, baseline characteristics were similar in men with or without such new unconfirmed lesions detected on follow-up bone scans. Therefore, men who are likely to have pseudoprogression cannot presently be identified prospectively, and data suggest that all men be carefully observed over time for this phenomenon.…”
Section: Research Original Investigationmentioning
confidence: 99%